'As a woman I cannot just leave the house': gendered spaces and HIV vulnerability in marriages in Kenya. Issue 8 (17th November 2018) - Njiru, Roseanne; Purkayastha, Bandana
Abstract: This article analyses how spaces are implicated in extramarital sex and HIV transmission in marriage. Drawing on the experiences and practices of married women and men in Kenya, we demonstrate how intersectionality is expressed through the social organization of space to shape particular patterns of femininity and masculinity and enable, mostly, men's infidelity and the possibility of the HIV risk. HIV mitigation policies focus mostly on altering individual-level behaviours but we argue that the invisibility of space in the sociology of gender, and in gender and HIV research, limits our analysis of the production and organization of extramarital sex as a key pathway to HIV infection in marriage. Therefore, our understanding of the gendered dimensions of HIV transmission in marriage may be improved by considering the socio-spatial structures within which marital infidelity occurs and move public health HIV interventions beyond individual-level interventions.